Perbandingan Pressure dan Velocity Terhadap Improvement Sistem Pendistribusian Air Penyiraman Tanaman Kangkung - Muhamad Hanhan Nugraha; Dede Abdulah Rinjani; Ridwan Maulana R; Abd Rohman (Motor Bakar : Jurnal Teknik Mesin, 2023)
The water distribution system on agricultural land is one factor that determines agricultural yields. The land in the Mekar Jaya Farmer Group, Cikupa Village, Karangnunggal District, Tasikmalaya Regency is rainfed land constrained in watering the land planted with kale. The sprinkling system that has been made uses a booster pump to drain the sprinkling water in the piping system, which has been arranged in such a way and is still constrained by an uneven distribution at some points so that the watering is not optimal so in this study improvements will be made with experimental methods and simulations on the device software by changing the T joint (T knee) which has an angle of 90° to a 45° angle. The simulation results show a significant change in pressure from 3.08 Pa at a 90° T joint to 9.63 Pa at a T joint at 45°.